Women in the medieval Spanish epic & lyric traditions - Sponsler, Lucy A. (Studies in Romance languages (Lexington, Ky.), 1975)
The culture of medieval Spain was anything nut homogeneous. It varied not only through time, with the approach of the Renaissance, but also geographically, with great differences between north and south. In this study, author Lucy A. Sponsler illuminates the role of women during this interesting period by exploring their portrayal in literature. Women in the Medieval Spanish Epic and Lyric Traditions examines the various ways in which women were portrayed in the formative years of medieval society, as well as the development of these views as new social mores evolved. Employing a thorough exam.